Positive impact of a tower inlet cover on natural draft dry cooling towers under crosswind conditions. (5th July 2018) - Liu, Quanlong; Xia, Lin; Hu, Mengqi; Li, Xiaoxiao; Mi, Zihao; Jia, Junjie
Highlights: A cover to improve the NDDCT performance under crosswind conditions is presented. The impact of crosswind on vortex formation inside NDDCT is explained. The working mechanism of the cover and its effects are presented. 4.5 m cover improves the tower heat load by 85–230% under crosswind conditions. Abstract: This study proposes a tower inlet cover to improve the performance of the small natural draft dry cooling tower (NDDCT) under crosswind conditions. CFD analyses are performed on a small NDDCT with tower inlet covers of different lengths, and the CFD model is validated against experimental results. The air temperature, air pressure, air flow and heat flux fields are presented, and the thermal performance for each heat exchanger and the NDDCT are obtained using CFD simulations. The CFD simulation results show that the high-pressure zone around the tower side wall, formed by the crosswind, causes the decrease in air flow through the tower and the deterioration in tower performance with a crosswind. The tower inlet cover can improve the tower performance in crosswinds by increasing the air flow of the heat exchangers. Tower inlet covers with lengths of 1.5 m, 3 m and 4.5 m improve the tower heat load by 40–65%, 70–130% and 85–230%, respectively, when the crosswind increases from 4 m/s to 12 m/s.